Stretched liquid crystal polymer film, laminate, circuit board, and method for producing liquid crystal polymer film
By combining heating and pressurization, hot air expansion and support polymer lamination during the stretching process of liquid crystal polymer film, the problems of breakage and high surface roughness during the stretching process are solved, and high frequency signal transmission loss is achieved and improve communication performance.
Patent Information
- Application Number
- CN202380049005.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-03
- Filing Date
- 2023-06-26
- Publication Date
- 2025-02-07
AI Technical Summary
The existing liquid crystal polymer films are prone to break during stretching and have high surface roughness, resulting in an increase in high-frequency signal transmission loss, affecting the rapid and large-capacity of communication.
By heating and pressing between the ring pairs of the double-belt press, or blowing hot air into the inflation mold to expand the film, and stretching in a vertical direction above the melting point of the liquid crystal polymer, combined with support polymerization The surface roughness of the material film is controlled to be 0.5 μm or less.
The smoothness and tensile resistance of the liquid crystal polymer film are improved, the transmission loss of high-frequency signals is reduced, and the communication speed and capacity are supported.
Smart Images

Figure CN119403676A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a stretched liquid crystal polymer film, a laminate, a circuit substrate and a method for producing the liquid crystal polymer film. Background Art
[0002] With the progress of mobile communication technology, the communication speed and capacity are being promoted, and the frequency used in communication is becoming higher. In the fifth generation mobile communication system, the 3.7GHz band and 4.5GHz band of the Sub6 band and the 28GHz band of the millimeter wave band are used, and in the sixth generation mobile communication system, the frequency band in the range of 90GHz to 300GHz is studied. The higher the frequency of the signal flowing through the circuit, the greater the transmission loss. Therefore, circuits and circuit materials with less transmission loss are sought.
[0003] The devices used in mobile communications such as smart phones are required to be miniaturized and lightweight, so a lightweight and freely bendable flexible printed circuit board (FPC) is used. The FPC is composed of a conductor such as a copper wire through which the signal passes and an insulating material to hold it. As the insulating material, a lightweight and flexible polymer film is used. For the polymer film, not only heat resistance that can be used continuously in a high temperature environment is required, but also a low dielectric constant and dielectric loss tangent are required to suppress the transmission loss when a high-frequency signal flows (for example, non-patent document 1).
[0004] As polymer films with low dielectric constant and low dielectric loss tangent used in FPC, there are polyimide films and liquid crystal polymer films. However, polyimide films have excellent heat resistance and bendability, but on the other hand, they have high water absorption and large dimensional change rate due to moisture absorption, so the connection reliability in the circuit formed with fine pitch patterns is low. Therefore, the development of FPC using liquid crystal polymer films with excellent heat resistance, low water absorption and small dimensional change rate is currently being promoted.
[0005] Liquid crystal polymer has the property of easy molecular orientation in its flow direction. In the melt extrusion method as a general manufacturing method of the film, the polymer is melted and extruded from a T die head to form a film. Therefore, the liquid crystal polymer of the film manufactured by this method is molecularly oriented along the length direction of the film. Therefore, in the film manufactured by this method, the film properties (strength, linear expansion coefficient, etc.) are greatly different in the length direction of the film and in the direction perpendicular to it, becoming a so-called large anisotropy state. On the other hand, FPC is manufactured as follows: copper foil is attached to a polymer film, or copper plating is implemented on a polymer film and a metal layer is stacked, and a wiring pattern is formed by etching, etc., thereby manufacturing. At this time, if the expansion rate (linear expansion coefficient) of the polymer film and the metal layer is different, the following undesirable conditions will occur: the insulating film and the metal layer will peel off according to temperature changes, or warping will occur in the FPC, or the hole will be misaligned after the FPC is subjected to a hole opening process. In this way, if a liquid crystal polymer film with large anisotropy is used as the insulating material of the FPC, the linear expansion coefficient will be greatly different according to the direction, so the above-mentioned undesirable conditions are easily generated.
[0006] As a method for reducing the anisotropy of a polymer film such as a polyethylene terephthalate (PET) film, a method of stretching the film in a direction perpendicular to the molecular orientation at a temperature above the glass transition temperature and below the melting point of the polymer film is used. However, a liquid crystal polymer film extruded from a T-die has a significantly low tensile strength, particularly in a direction perpendicular to the molecular orientation. Therefore, when the film is stretched in a direction perpendicular to the molecular orientation direction at a temperature below the melting point of the liquid crystal polymer, it is prone to breakage.
[0007] Therefore, the following methods have been proposed: a method of heating and pressurizing a liquid crystal polymer film extruded from a T-die between a pair of endless belts of a double-belt press (for example, Patent Document 1); a method of extruding a liquid crystal polymer film in a cylindrical shape from a blow mold and blowing hot air to expand the film before it cools and solidifies (for example, Patent Document 2); a method of heating and laminating a porous polytetrafluoroethylene (PTFE) film to both sides of a liquid crystal polymer film extruded from a T-die, and stretching the film in a direction perpendicular to the longitudinal direction at a temperature above the melting point of the liquid crystal polymer film (for example, Patent Document 3); etc.
[0008] In addition, due to the skin effect, the higher the frequency of the signal flowing through the conductor, the more it flows through the conductor surface. For example, the skin depth δ of the signal flowing through the conductor is as follows: when the magnetic permeability of the conductor is μ, the electrical conductivity is σ, and the frequency of the signal flowing through the conductor is f, it is expressed as the following formula (1) (for example, non-patent document 2). In addition, when copper is used as the conductor, μ is set to 5.90×10 7 (H / m),σ=1.26×10 -6(S / m), and the skin depth δ when f is from 1 GHz to 300 GHz is obtained as Figure 1 Like that. In the 5th generation mobile communication system, at 3.7GHz in the Sub6 frequency band, the skin depth δ is about 1.1μm, but at 28GHz in the millimeter wave band, the skin depth δ is about 0.4μm. Therefore, the greater the depth of the concave and convex on the conductor surface and the shorter the interval between the concave and convex, even for the same length of conductor, the longer the distance the signal flows, and the greater the transmission loss. Therefore, high smoothness is required for the conductor surface, and the conductor surface of the FPC for the millimeter wave band (about 30 to 300GHz) to be used in future mobile communication systems is required to have a surface roughness Ra of less than 0.5μm.
[0009]
[0010] Moreover, the smoothness of the polymer film surface of the laminated conductor also has an impact on the smoothness of the conductor surface. In particular, when a metal layer is formed on the polymer film surface by evaporation, electrolytic plating, or chemical plating to make FPC, the polymer film requires the same degree of smoothness as the conductor. As a method for improving the smoothness of polymer film, for example, when a metal layer is formed on the polymer film surface by chemical plating, in order to reduce the surface roughness of the polymer film surface and improve the adhesion with the metal layer, the following method can be cited: a mixed solution of an alkali aqueous solution and amyl alcohol is contacted with the polymer film surface. However, in this method, when the roughness of the polymer film surface is large, the contact time with the mixed solution of an alkali aqueous solution and amyl alcohol must be extended, not only the production efficiency is reduced, but also the strength of the film is reduced. Therefore, it is desirable to have a liquid crystal polymer film with a small surface roughness even if such a treatment is not implemented.
[0011] Prior art literature
[0012] Non-patent literature
[0013] Non-patent document 1: Matsushita Yukio et al., "Substrate Materials for High-Speed Transport", Journal of the Electronic Packaging Society, Vol. 4, No. 7, p. 551, 2001
[0014] Non-patent document 2: Nakata Shinya et al., Fukuda Technical Report (October 2021)
[0015] Patent Literature
[0016] Patent Document 1: Japanese Patent No. 6930046
[0017] Patent Document 2: Japanese Patent No. 6656231
[0018] Patent Document 3: Japanese Patent No. 3958629 Summary of the invention
[0019] Problem that the invention aims to solve
[0020] The liquid crystal polymer film is extruded into a cylindrical shape from a blow mold, and in the existing method of blowing hot air to expand before the film is cooled and solidified, although the anisotropy of the liquid crystal polymer can be eliminated, the thickness of the film is uneven and the concavoconvexity of the film surface becomes larger due to the uneven temperature of the film during expansion. Furthermore, while the porous polytetrafluoroethylene (PTFE) film is heated and attached to the two sides of the liquid crystal polymer film extruded from the T die head, in the method of stretching at a temperature above the melting point of the liquid crystal polymer film and in a direction perpendicular to the length direction, the liquid crystal polymer is stretched above the melting point, so it is difficult to control the thickness of the film. In addition, the concavoconvexity of the surface of the porous PTFE is transferred to the liquid crystal polymer film, so the smoothness is poor. Patent document 3 discloses a liquid crystal polymer film with a surface roughness Ra of less than 0.1 μm, but it is measured by a contact surface roughness measuring device. For a contact surface roughness meter, a stylus is brought into contact with the surface of the film, and the stylus is traced on the surface while detecting the change (displacement) in the up and down direction of the stylus. The tip diameter of the stylus is as small as about 2 μm, so it is impossible to measure the roughness of uneven surfaces with finer intervals than this. Therefore, the smoothness of the polymer film surface cannot be fully evaluated in the contact type surface roughness meter, and when the liquid crystal polymer film described in Patent Document 3 is used for FPC, there is a concern that the transmission loss of high-frequency signals will increase.
[0021] The object of the present invention is to provide a liquid crystal polymer film with high smoothness that can provide an FPC with low transmission loss when a high-frequency signal flows through it when used as an insulating material for an FPC, especially when a metal layer is formed on the surface by vapor deposition, electrolytic plating, or chemical plating to make an FPC.
[0022] Solutions for solving problems
[0023] The present inventors have conducted in-depth research on liquid crystal polymer films that have low transmission loss and high smoothness when high-frequency signals flow through them. As a result, they found that by appropriately controlling the surface roughness measured by a laser microscope, a liquid crystal polymer film with excellent smoothness that reflects the fine bumps and depressions on the film surface can be obtained, thereby completing the present invention.
[0024] [1] That is, according to a first aspect of the present invention, there is provided a stretched liquid crystal polymer film, which is a stretched liquid crystal polymer film formed of a liquid crystal polymer, wherein the surface roughness Ra of at least one surface of the stretched liquid crystal polymer film measured by a laser microscope is 0.5 μm or less.
[0025] [2] According to a second aspect of the present invention, there is provided a stretched liquid crystal polymer film, which is a stretched liquid crystal polymer film formed by a liquid crystal polymer, wherein for at least one side, the larger of the surface roughness Ra (MD) in the length direction and the surface roughness Ra (TD) in the width direction of the film measured by a laser microscope is less than 0.7 μm, and the absolute value of the difference between the aforementioned Ra (MD) and the aforementioned Ra (TD) is less than 0.15 μm.
[0026] [3] According to the third aspect of the present invention, there is provided a stretched liquid crystal polymer film of the first or second aspect, wherein, in a pole measurement based on X-ray diffraction, when the film is tilted at 45° (α=45° in the Schulz method) and the diffraction intensity of the 110 plane is measured while the film is rotated along the in-plane direction, i.e., the β direction, the longitudinal direction of the film is set to β=0°, and the integrated intensities of β=45-135°, 135°-225°, 225-315°, and 315-45° are obtained, and when the sum of the integrated intensity of β=45-135° and the integrated intensity of β=225°-315° is the integrated intensity in the longitudinal direction, and the sum of the integrated intensity of β=135-225° and the integrated intensity of β=315-45° is the integrated intensity in the width direction, the plane orientation degree represented by the following formula (2) is greater than -0.5 and less than 0.5.
[0027] Planar orientation degree = (integrated intensity in the length direction - integrated intensity in the width direction) / (integrated intensity in the length direction + integrated intensity in the width direction) (2)
[0028] [4] According to a fourth aspect of the present invention, there is provided a method for producing a stretched liquid crystal polymer film, which comprises the following steps: a first step of laminating a support film formed by a support polymer and having a surface roughness Ra of less than 1.5 μm as measured by a laser microscope to at least one side of an unstretched liquid crystal polymer film formed by a liquid crystal polymer to obtain a laminated film; a second step of stretching the laminated film at least in the width direction; and a third step of peeling off the stretched support film.
[0029] [5] According to the fifth aspect of the present invention, there is provided a method for producing a stretched liquid crystal polymer film, which comprises the following steps: a first step of using an extruder to extrude a molten liquid crystal polymer and a supporting polymer into a film in a manner such that a layer formed by the aforementioned supporting polymer is stacked on at least one side of a layer formed by the aforementioned liquid crystal polymer, thereby obtaining a laminated film; a second step of stretching the aforementioned laminated film at least in the width direction; and a third step of peeling off the stretched layer formed by the aforementioned supporting polymer.
[0030] [6] According to the sixth aspect of the present invention, a method for manufacturing a stretched liquid crystal polymer film is provided, which is the method for manufacturing a stretched liquid crystal polymer film of the fourth aspect, wherein the first step includes the following steps: before bonding the support film to the unstretched liquid crystal polymer film, surface treatment is performed on the surface to be bonded of the unstretched liquid crystal polymer film and the surface to be bonded of the support film.
[0031] [7] According to the seventh aspect of the present invention, there is provided a method for producing a stretched liquid crystal polymer film, which is the method for producing a stretched liquid crystal polymer film according to the sixth aspect, wherein the surface treatment is one selected from the group consisting of plasma treatment, corona treatment and chemical treatment.
[0032] [8] According to the eighth aspect of the present invention, there is provided a method for manufacturing a stretched liquid crystal polymer film, which is a method for manufacturing a stretched liquid crystal polymer film according to any one of the fourth to seventh aspects, wherein the second step comprises the following steps: stretching at a temperature lower than the melting point of the liquid crystal polymer.
[0033] [9] According to the 9th aspect of the present invention, there is provided a method for manufacturing a stretched liquid crystal polymer film, which is the method for manufacturing a stretched liquid crystal polymer film according to the 4th, or any one of the 6th to 8th aspects, wherein, in the aforementioned second step, the tensile load calculated by multiplying the tensile stress of the aforementioned support film at the temperature during stretching by the cross-sectional area of the aforementioned support film is greater than or equal to the tensile load calculated by multiplying the tensile stress of the aforementioned unstretched liquid crystal polymer film at the temperature during stretching by the cross-sectional area of the aforementioned unstretched liquid crystal polymer film.
[0034]
[10] According to the tenth aspect of the present invention, there is provided a method for manufacturing a stretched liquid crystal polymer film, which is the method for manufacturing a stretched liquid crystal polymer film of the fifth aspect, wherein, in the aforementioned second step, the tensile load calculated by multiplying the tensile stress of the layer formed by the aforementioned supporting polymer at the temperature during stretching by the cross-sectional area of the layer formed by the aforementioned supporting polymer is greater than or equal to the tensile load calculated by multiplying the tensile stress of the layer formed by the aforementioned liquid crystal polymer at the temperature during stretching by the cross-sectional area of the layer formed by the aforementioned liquid crystal polymer.
[0035]
[11] According to the 11th aspect of the present invention, there is provided a method for producing a stretched liquid crystal polymer film, which is the method for producing a stretched liquid crystal polymer film according to any one of the 4th to 10th aspects, wherein the supporting polymer is an aromatic polyether ketone or a polyester.
[0036]
[12] According to the twelfth embodiment of the present invention, there is provided a method for producing a stretched liquid crystal polymer film, which is the method for producing a stretched liquid crystal polymer film according to the eleventh embodiment, wherein the aforementioned polyester is at least one polymer selected from the group consisting of polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate.
[0037]
[13] According to a thirteenth aspect of the present invention, there is provided a laminate comprising: a film layer comprising the stretched liquid crystal polymer film according to any one of the first to third aspects; and a metal layer.
[0038]
[14] According to a fourteenth aspect of the present invention, there is provided a circuit board comprising the laminated body according to the thirteenth aspect.
[0039] Effects of the Invention
[0040] The stretched liquid crystal polymer film of the present invention has a surface roughness Ra of 0.5 μm or less on at least one side measured by a laser microscope. Therefore, when used as an insulating material for FPC, transmission loss when high-frequency signals flow therethrough is reduced, making it possible to increase communication speed and capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a graph showing the relationship between the frequency of a signal flowing on the surface of the copper foil and the skin depth through which the signal flows.
[0042] Figure 2 (a) is a diagram comparing the sizes of the concavities and convexities measured by a contact surface roughness meter and a laser microscope. Figure 2 (b) is a diagram comparing the sizes of micro-spaced concavities and convexities measured by a contact-type surface roughness meter and a laser microscope.
[0043] Figure 3 This is a graph comparing the tensile load of the unstretched liquid crystal polymer film and the tensile load of the PEEK film in Example 1 according to the embodiment of the present invention.
[0044] Figure 4 This is a graph comparing the tensile load of the unstretched liquid crystal polymer film and the tensile load of the porous PTFE film in Comparative Example 2. DETAILED DESCRIPTION
[0045] <Liquid Crystal Polymer Film>
[0046] The stretched liquid crystal polymer film of the present invention is a film formed of a liquid crystal polymer. The liquid crystal polymer is not particularly limited, but preferably shows thermotropic liquid crystal properties and has a melting point of 250°C or more, preferably 280°C to 380°C. As such a liquid crystal polyester, for example, an aromatic polyester synthesized from monomers such as aromatic diols, aromatic carboxylic acids, and hydroxycarboxylic acids, which shows liquid crystal properties when melted. Specifically, examples include: polycondensates of ethylene terephthalate and p-hydroxybenzoic acid, polycondensates of phenol, phthalic acid, and p-hydroxybenzoic acid, polycondensates of 2,6-hydroxynaphthoic acid and p-hydroxybenzoic acid, and the like. From the viewpoint of excellent mechanical properties, electrical properties, heat resistance, etc., it is preferred to use an aromatic polyester-based liquid crystal polymer having 6-hydroxy-2-naphthoic acid and its derivatives as a basic structure and having at least one selected from the group consisting of p-hydroxybenzoic acid, terephthalic acid, isophthalic acid, 6-naphthalenedicarboxylic acid, 4,4'-biphenol, bisphenol A, hydroquinone, 4,4-dihydroxybiphenol, ethylene terephthalate and their derivatives as a monomer component. It should be noted that the liquid crystal polyesters can be used alone or in any combination and ratio.
[0047] The synthesis method of the liquid crystal polyester can be a known method without particular limitation, and can be, for example, melt polymerization, melt acid hydrolysis, slurry polymerization, etc. When these polymerization methods are used, acylation or acetylation can be carried out according to conventional methods.
[0048] Liquid crystal polymers may include polymers such as fluororesins, polyolefins, polycycloolefins, release modifiers such as higher fatty acids, higher fatty acid esters, higher fatty acid amides, and higher fatty acid metal salts having carbon numbers of 10 to 25, dyes, pigments, colorants such as carbon black, organic fillers, inorganic fillers, hollow particles, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, flame retardants, lubricants, antistatic agents, surfactants, rust inhibitors, foaming agents, defoamers, fluorescent agents, and other additives within the range that does not excessively impair the effects of the present invention. These polymers and additives may be included in the molten resin composition when the liquid crystal polymer film is formed. In addition, these polymers and additives may be used alone or in combination of two or more. The content of polymers and additives is not particularly limited. From the viewpoints of molding processability, thermal stability, etc., it is preferably 0.01 to 50% by mass, more preferably 0.1 to 40% by mass, and further preferably 0.5 to 30% by mass relative to the total amount of the liquid crystal polymer film. These polymers, additives, and the like may be added to the liquid crystal polymer in advance, or may be added to the liquid crystal polymer when forming a stretched liquid crystal polymer film described later.
[0049] The surface roughness Ra of one or both sides of the stretched liquid crystal polymer film of the present invention measured by a laser microscope is less than 0.5 μm. The surface roughness Ra in the present invention is specifically the arithmetic mean roughness of the film surface measured by non-contact method based on the confocal principle that the amount of reflected light becomes the maximum when the focus is aligned.
[0050] Figure 2 (a) is a diagram comparing the sizes of the concavities and convexities measured by a contact surface roughness meter and a laser microscope. Figure 2 (b) is a diagram comparing the sizes of micro-spaced concavities and convexities measured by a contact-type surface roughness meter and a laser microscope.
[0051] like Figure 2 As shown in (a), for the concave-convex (recess) with an interval (W1) into which the stylus (N) of the contact type surface roughness measuring instrument can enter, the size (depth) (D1-N) of the concave-convex measured by the contact type surface roughness measuring instrument and the size (D1-L) of the concave-convex measured by the laser microscope (L) become substantially the same size. Therefore, when the surface (S1) of the measuring object mainly has concave-convex with such intervals, it is considered that there is no large difference in the surface roughness values measured by the respective methods.
[0052] However, if Figure 2 As shown in (b), when there are very small concave-convex intervals (W2) on the surface (S2) of the measured object, in the contact type surface roughness measuring device, the width of the stylus is wider than the width of the concave-convex intervals and cannot enter the inside of the concave-convex intervals. Therefore, in the contact type surface roughness measuring device, the size (D2-N) of the concave-convex intervals actually measured will be smaller than that of the concave-convex intervals, or it will be ignored, and the value of the surface roughness will become smaller than the actual value. On the other hand, in the measurement based on the laser microscope, the laser can also enter the concave-convex intervals of the small intervals, so the accurate size (D2-L) of the concave-convex can be measured. Therefore, in the measurement of the surface roughness based on the laser microscope, compared with the existing contact type surface roughness measurement, the accurate surface roughness evaluation reflecting the concave-convex shape of the smaller intervals can be performed. In particular, high-frequency signals can also enter the concave-convex intervals of such small intervals. Therefore, when the liquid crystal polymer film is used for FPC, in order to reduce the transmission loss of the high-frequency signal, it is extremely important to control the surface roughness of the liquid crystal polymer film measured by the laser microscope.
[0053] The stretched liquid crystal polymer film of the present invention is measured by a laser microscope. The surface roughness Ra of at least one side is less than 0.5 μm, so that the film is bonded to the conductor and the laminate is manufactured. The interface between the film and the conductor becomes smooth, and the transmission loss when the high-frequency signal flows through is suppressed. Therefore, the high-speed and high-capacity communication based on the laminate becomes possible. It should be noted that the surface roughness Ra can be measured along any direction of the surface of the stretched liquid crystal polymer film. That is, as long as the surface roughness Ra measured in any direction is less than 0.5 μm, it is preferred that the average of the surface roughness Ra measured multiple times in any direction is less than 0.5 μm. In addition, it is preferred that the surface roughness Ra measured along the length direction (MD) or width direction (TD) of the film is less than 0.5 μm, and more preferably the surface roughness Ra (MD) measured along the length direction and the surface roughness Ra (TD) measured along the width direction are both less than 0.5 μm. It is particularly preferred that the average of the surface roughness Ra (MD) obtained by measuring multiple times in the length direction is less than 0.5 μm, and the average of the surface roughness Ra (TD) obtained by measuring multiple times in the width direction is less than 0.5 μm. In addition, when the conductor is attached to both sides of the stretched liquid crystal polymer film, from the viewpoint of being able to suppress the transmission loss of the two conductors, it is more preferred that the surface roughness Ra of both sides of the stretched liquid crystal polymer film measured by a laser microscope is less than 0.5 μm. The surface roughness Ra of the surface of the stretched liquid crystal polymer film is preferably less than 0.4 μm in any direction and on any surface, and particularly preferably less than 0.2 μm. If Ra is less than 0.2 μm, the skin depth of the 90 GHz signal studied in the 6th generation mobile communication system when flowing through the surface of the copper is less than 0.22 μm, and the transmission loss is reduced.
[0054] In addition, the stretched liquid crystal polymer film of the present invention can suppress the transmission loss of high-frequency signals as described above by making the larger of the surface roughness Ra (MD) in the longitudinal direction and the surface roughness Ra (TD) in the width direction less than 0.7 μm for at least one side, and the absolute value of the difference between the surface roughness Ra (MD) and the surface roughness Ra (TD) less than 0.15 μm. In addition, when manufacturing a circuit substrate using the stretched liquid crystal polymer film of the present invention by the circuit substrate manufacturing method described later, the conductor of the non-wiring portion formed on the film can be removed with a small amount of etching, and the influence of etching on the wiring portion can be reduced, so that a circuit substrate with a precise circuit can be manufactured. In such a stretched liquid crystal polymer film, the larger of the surface roughness Ra (MD) and the surface roughness (TD) is less than 0.7 μm, preferably less than 0.5 μm, more preferably less than 0.4 μm, and further preferably less than 0.2 μm. In addition, the absolute value of the difference between the surface roughness Ra (MD) and the surface roughness Ra (TD) is less than 0.15 μm, preferably less than 0.1 μm, and more preferably less than 0.05 μm. It should be noted that the surface roughness Ra (MD) and the surface roughness Ra (TD) only need to satisfy the above relationship as long as the values obtained by measuring at least once on one side of the stretched liquid crystal polymer film. Preferably, the average of the surface roughness Ra (MD) and the average of the surface roughness Ra (TD) obtained by multiple measurements satisfy the above relationship. In addition, for both sides of the stretched liquid crystal polymer film, it is preferred that the surface roughness Ra (MD) and the surface roughness Ra (TD) satisfy the above relationship.
[0055] The anisotropy of the molecular orientation of the stretched liquid crystal polymer film is preferably within the prescribed range as specified below. First, in the extreme point measurement based on X-ray diffraction, the stretched liquid crystal polymer film is tilted at 45° (α=45° in the Schulz method), and the diffraction intensity of the 110 plane is measured while the film is rotated along the in-plane direction (β direction) to prepare an X-ray diffraction intensity curve. In this curve, the longitudinal direction of the film is β=0°, and the integrated intensity of β=45~135°, 135°~225°, 225~315°, and 315~45° is obtained, and the sum of the integrated intensity at β=45~135° and the integrated intensity at β=225°~315° is the integrated intensity in the longitudinal direction. In addition, the sum of the integrated intensity at β=135~225° and the integrated intensity at β=315~45° is the integrated intensity in the width direction. In this case, the plane orientation degree represented by the following formula (2) is preferably from -0.5 to 0.5. The plane orientation degree is preferably from -0.3 to 0.3, and more preferably from -0.2 to 0.2.
[0056] Planar orientation degree = (integrated intensity in the length direction - integrated intensity in the width direction) / (integrated intensity in the length direction + integrated intensity in the width direction) (3)
[0057] The diffraction intensity of the 110 plane refers to the diffraction intensity of the crystal plane (110 plane) of the liquid crystal polymer. For example, the diffraction intensity of the 110 plane in the liquid crystal polymer obtained by polycondensing 2,6-hydroxynaphthoic acid and p-hydroxybenzoic acid at a molar ratio of 73:27 refers to the maximum diffraction intensity observed at 2θ=20° when measuring X-ray diffraction within the range of diffraction angle (2θ) of 10° to 40°. For the diffraction intensity of the (110 plane) of the liquid crystal polymer oriented in the length direction, when the length direction of the film is β=0°, it is the maximum at β=90° and 270°. Therefore, the sum of the integrated intensity of β=45 to 135° and the integrated intensity of β=225° to 315° is the integrated intensity in the length direction, and the sum of the integrated intensity of β=135 to 225° and the integrated intensity of β=315 to 45° is the integrated intensity in the width direction. The integrated intensity is obtained from the area represented by β as the horizontal axis and the diffraction intensity as the vertical axis. A positive value represented by the above formula (3) indicates that the molecular chains are oriented in the longitudinal direction, while a negative value indicates that the molecular chains are oriented in the width direction.
[0058] The value of the plane orientation degree shown in the above formula (3) is greater than -0.5 and less than 0.5, so that the anisotropy of the linear expansion coefficient of the stretched liquid crystal polymer film of the present invention can be reduced. Therefore, when the stretched liquid crystal polymer film is stacked with copper to form an FPC, deformation caused by the difference in linear expansion coefficient can be suppressed. This effect is particularly significant when the stretched liquid crystal polymer film is subjected to a heat treatment (described later). The value of the plane orientation degree is preferably -0.2 to 0.2. If it is within this range, the linear expansion coefficient of the stretched liquid crystal polymer film can be about 10 to 30 ppm in both the length and width directions of the film, and the plane orientation degree is further made to be -0.1 to 0.1, so that the linear expansion coefficient becomes a value close to the linear expansion coefficient of copper, 18 ppm.
[0059] <Method for producing stretched liquid crystal polymer film>
[0060] The following is a method for producing a stretched liquid crystal polymer film of the present invention. The stretched liquid crystal polymer film of the present invention is obtained by laminating a supporting polymer film to both sides of an unstretched liquid crystal polymer film to form a laminated film (first step), stretching the laminated film (second step), and peeling off the supporting polymer film (third step).
[0061] The unstretched liquid crystal polymer film used in the first step can be manufactured by a known method. For example, by using a melt extrusion film-making method (T-die melt extrusion) using a T-die, the liquid crystal polymer is film-formed into a film, and an unstretched liquid crystal polymer film can be formed. Specifically, the liquid crystal polymer is melt-kneaded in an extruder, and the molten resin is extruded through a T-die, and solidified on a metal roller, thereby obtaining an unstretched liquid crystal polymer film. The temperature of the barrel of the extruder is preferably 230 to 360°C, more preferably 280 to 350°C. The slit spacing of the T-die can be appropriately set according to the type, composition, performance of the target film, etc. of the liquid crystal polymer used. The slit spacing of the T-die is not particularly limited, preferably 0.1 to 1.5 mm, more preferably 0.1 to 1.0 mm.
[0062] The thickness of the unstretched liquid crystal polymer film obtained by the above method is not particularly limited, but is preferably 10 to 500 μm, more preferably 20 to 300 μm, and even more preferably 30 to 250 μm from the viewpoint of operability and productivity during T-die melt extrusion molding.
[0063] The supporting polymer film is a film stacked on the unstretched liquid crystal polymer film to prevent the film from breaking when the unstretched liquid crystal polymer film is stretched. As the supporting polymer constituting the supporting polymer film, aromatic polyether ketone or polyester can be cited. As a specific example of aromatic polyether ketone, polyether ketone (PEK), polyether ether ketone (PEEK), polyether ketone ketone (PEKK), polyether ether ketone ketone (PEEKK), etc. can be exemplified. As a specific example of polyester, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc. can be exemplified. These polymers can be used alone or in combination of more than two. Among them, polyether ether ketone (PEEK), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) are preferred. Furthermore, when these films are crystallized or stretched films, they are preferably in terms of high heat resistance and being able to be stretched at high temperatures.
[0064] The surface roughness Ra of the supporting polymer film measured by laser microscopy is preferably 1.5 μm or less, more preferably 1.0 μm or less, further preferably 0.5 μm or less, and particularly preferably 0.2 μm or less. By making the surface roughness of the supporting polymer film within the above range, the surface roughness Ra of the obtained stretched liquid crystal polymer film measured by laser microscopy can be controlled to be 0.5 μm or less.
[0065] When stacking an unstretched liquid crystal polymer and a supporting polymer film, the supporting polymer film can be stacked only on one side or both sides of the unstretched liquid crystal polymer film. However, in terms of being able to control the surface roughness Ra of both sides of the obtained stretched liquid crystal polymer film to be less than 0.5 μm, and in terms of being able to reduce undesirable conditions such as breakage of the unstretched liquid crystal polymer film when the stacked film stacked with the unstretched liquid crystal polymer film and the supporting polymer film is stretched along the width direction (TD) in the second step described later, it is preferred to stack them on both sides.
[0066] As a method for laminating the unstretched liquid crystal polymer film to the supporting polymer film, there is no particular limitation. From the viewpoint of not requiring an adhesive, a heat lamination method is preferred. In the heat lamination method, the laminated film of the unstretched liquid crystal polymer film and the supporting polymer film is heated with a pair of heated rollers while the unstretched liquid crystal polymer film and the supporting polymer film are pressed. The conditions in the heat lamination method can be appropriately selected according to the physical properties of the liquid crystal polymer and the supporting polymer. There is no particular limitation. It is preferred to heat and press at a temperature near the melting point of the liquid crystal polymer and at a temperature near the melting point of the supporting polymer.
[0067] In the case where it is not easy to make the unstretched liquid crystal polymer film close to the supporting film only by heat lamination, it is preferred that before the unstretched liquid crystal polymer film is laminated to the supporting polymer film, the surface in the unstretched liquid crystal polymer film that contacts the supporting polymer film (laminated surface) and the surface in the supporting polymer film that contacts the unstretched liquid crystal polymer film (laminated surface) are respectively subjected to surface treatment. As a method for surface treatment, examples can be given: plasma treatment of a gas that provides electrical energy to the surface irradiation to form a plasma state, corona treatment that activates the surface by discharge, a method of activating the surface by irradiating ultraviolet rays and electron beams, a method of activating the surface by contacting a flame, a chemical treatment of oxidizing the surface using potassium dichromate, etc., a primer treatment of applying a primer, etc. By performing such a surface treatment before laminating the unstretched liquid crystal polymer film to the supporting polymer film, the adhesion of the unstretched liquid crystal polymer film to the supporting polymer film can be improved. The surface treatment method can be appropriately selected according to the physical properties of the liquid crystal polymer and the supporting polymer, but from the viewpoint of improving the adhesion between the unstretched liquid crystal polymer film and the supporting polymer film and reducing the damage to the obtained stretched liquid crystal polymer film, plasma treatment, corona treatment, and chemical treatment are preferred, and plasma treatment is particularly preferred.
[0068] In addition, as a method for improving the adhesion between the unstretched liquid crystal polymer film and the supporting polymer film, there is also a method of providing an easy-adhesion layer composed of a polyester resin material on the surface of the supporting polymer film.
[0069] Next, as the second step, the laminated film laminated with the unstretched liquid crystal polymer film and the supporting polymer film is stretched in the width direction (TD). By stretching the laminated film in the width direction, the anisotropy of the obtained stretched liquid crystal polymer film can be reduced. As a method for stretching the laminated film, there is no particular limitation, and it is preferred to use a tenter transverse stretching method in which the two ends of the laminated film are clamped by a clamp and heated and stretched. For the stretching ratio and the stretching speed, it is appropriately selected in a manner that the supporting film can be stretched and the shape and physical properties of the film formed by the liquid crystal polymer after stretching are in the desired range. The stretching ratio is preferably 1.5 to 10 times, more preferably 2 to 5 times. The stretching speed is preferably 1 to 5000% / minute, more preferably 50 to 2500% / minute. In addition, in order to adjust the degree of plane orientation after stretching, stretching in the length direction (MD) can also be added as needed.
[0070] The temperature when the laminated film is stretched is preferably set in the range of 50 to 350°C, more preferably set to a temperature lower than the melting point of the liquid crystal polymer, further preferably set to a temperature 30 to 200°C lower than the melting point of the liquid crystal polymer, and particularly preferably set to a temperature 80 to 200°C lower than the melting point of the liquid crystal polymer. By setting the temperature when the laminated film is stretched to a temperature lower than the melting point of the liquid crystal polymer, the smoothness of the obtained stretched liquid crystal polymer film can be improved, and the film forming property can be excellent without uneven thickness and stripes. Furthermore, by setting the temperature when the laminated film is stretched to a temperature above the glass transition temperature of the liquid crystal polymer, the unstretched liquid crystal polymer film becomes easy to stretch, so it is more preferred.
[0071] In addition, it is preferred that during the stretching of the laminated film, the total of the tensile loads applied to the two supporting polymer films laminated on both sides of the unstretched liquid crystal polymer film is usually equal to or greater than the tensile load applied to the unstretched liquid crystal polymer film. Here, the tensile load refers to the load applied to the film when the film is stretched, and is a value obtained by multiplying the tensile stress of the film by the cross-sectional area of the film.
[0072] During the stretching of the laminated film, the total tensile load applied to the two supporting polymer films is made equal to or greater than the tensile load applied to the unstretched liquid crystal polymer film, so that the unstretched liquid crystal polymer film can be stretched without breaking even at a temperature lower than the melting point of the liquid crystal polymer. The reason for this is not clear, but it is believed that this is because the tensile load applied to the liquid crystal polymer film is dispersed by making the supporting polymer film with a higher tensile load than the unstretched liquid crystal polymer film closely attached to the unstretched liquid crystal polymer film, thereby suppressing stress concentration on the portion that is likely to cause breakage.
[0073] It should be noted that, in order to make the total tensile load applied to the two supporting polymer films equal to or greater than the tensile load applied to the unstretched liquid crystal polymer film, this can be achieved by appropriately selecting the ratio of the thickness of the unstretched liquid crystal polymer film to the thickness of the supporting polymer film, the material and surface roughness of the supporting polymer film, and the temperature and stretching speed during stretching. For example, the material of the supporting polymer film can be selected based on the temperature during stretching determined by the type of liquid crystal polymer.
[0074] When using a laminated film in which a supporting polymer film is laminated only on one side of an unstretched liquid crystal polymer film, the laminated film may be stretched so that the tensile load applied to one supporting polymer film is equal to or greater than the tensile load applied to the unstretched liquid crystal polymer film.
[0075] From the viewpoint of being able to well adjust the relationship between the tensile load applied to the supporting polymer film and the tensile load applied to the unstretched liquid crystal polymer film, the thickness ratio of the supporting polymer film to the unstretched liquid crystal polymer film is calculated as "the thickness of one supporting polymer film / the thickness of the unstretched liquid crystal polymer film", and is preferably set to 0.01 to 10.0, more preferably to 0.1 to 1.0, and further preferably to 0.2 to 0.8.
[0076] Finally, as a third step, the supporting polymer film of the stretched laminated film is peeled off to obtain a stretched liquid crystal polymer film.
[0077] In the third step, after the supporting polymer film is peeled off, the stretched liquid crystal polymer film may be heat treated in the range of -50°C from its melting point to its melting point. This can improve the heat resistance of the liquid crystal polymer film and reduce the linear expansion coefficient.
[0078] It should be noted that in the above method, a laminated film is obtained by laminating a film formed by a liquid crystal polymer and a film formed by a supporting polymer in the first step, but the method for obtaining the laminated film is not particularly limited thereto. For example, while the liquid crystal polymer is melted in the first extruder, the supporting polymer is melted in the second extruder, and each polymer is extruded into a film (coextrusion) in a manner that a layer formed by the supporting polymer is laminated on one or both sides of the layer formed by the liquid crystal polymer, thereby forming a laminated film.
[0079] As a method for laminating a layer formed by a supporting polymer on one or both sides of a layer formed by a liquid crystal polymer, a molding method of a multilayer extruded film from a T-die can be used. Specifically, the following methods can be cited: a feed head method in which a molten liquid crystal polymer and a supporting polymer supplied from two extruders are supplied to a feed head and merged, and then extruded into a film-like film from a T-die; a multi-manifold method in which a molten liquid crystal polymer and a supporting polymer are respectively supplied to a T-die, overlapped into a film-like film and extruded; etc. From the viewpoint of improving the smoothness of the obtained stretched liquid crystal polymer film, considering the different viscosity and flow characteristics of the liquid crystal polymer and the supporting polymer when melted, it is preferred to apply a multi-manifold method.
[0080] In the case where a laminated film is formed by extruding a liquid crystal polymer and a supporting polymer into film forms respectively in the first step, it is preferred that the laminated film be stretched in the second step in such a manner that the tensile load applied to the layer formed by the supporting polymer becomes greater than or equal to the tensile load applied to the layer formed by the liquid crystal polymer.
[0081] <Laminate>
[0082] The laminate of the present invention comprises a film layer formed of the stretched liquid crystal polymer film and a metal layer. Examples of metal materials constituting the metal layer include gold, silver, copper, iron, nickel, aluminum, and alloys thereof, and copper is preferably used.
[0083] As long as the smoothness and anisotropy of the stretched liquid crystal polymer film can be maintained, the laminate can be manufactured according to a known method. For example, the laminate can be manufactured by evaporating a metal layer on the surface of the stretched liquid crystal polymer film, and the metal layer can be formed on the surface of the stretched liquid crystal polymer film by chemical plating or electrolytic plating. In addition, a metal foil such as copper foil can be overlapped with a stretched liquid crystal polymer film and a metal foil by a roll-to-roll type or a continuous isostatic pressing type (double belt type), and hot pressing is continuously performed to manufacture a laminate. In addition, the laminate can be manufactured by removing oxides and dirt by methods such as sputtering etching to activate the surface of the stretched liquid crystal polymer film and the metal foil, and the stretched liquid crystal polymer film is abutted against the metal foil and rolled to form a surface activated bonding bonded thereto.
[0084] <Circuit Board>
[0085] The circuit substrate of the present invention comprises an insulator (or dielectric) and a conductor layer formed by the stretched liquid crystal polymer film. The form of the circuit substrate is not particularly limited, and it can be used as various high-frequency circuit substrates by known means. The circuit substrate can be equipped with semiconductor components such as IC chips.
[0086] A circuit pattern is formed on the conductor layer of the circuit substrate by a known processing method. Examples of metal materials constituting the conductor layer include gold, silver, copper, iron, nickel, aluminum, and alloys thereof. It should be noted that a circuit pattern can be formed on the metal layer of the laminate by a known method.
[0087] As a method for manufacturing a circuit substrate having a circuit pattern, specifically, there can be exemplified the following methods known in the past, such as a modified semi-additive method (MSAP method), a semi-additive method (SAP method), and a subtractive method. For example, in the case of the SAP method, chemical copper plating is applied to an insulator formed by a stretched liquid crystal polymer film as a conductor layer, the non-wiring portion on the conductor layer is masked, and electrolytic copper plating is applied to the unmasked portion to form an additional conductor layer, the mask is removed, and the conductor layer covered by the mask is removed by etching, thereby manufacturing a circuit substrate. In addition, in the case of the MSAP method, an extremely thin copper foil is laminated instead of chemical copper plating in the SAP method, thereby manufacturing a circuit substrate.
[0088] The manufacturing method of the circuit substrate such as the above-mentioned MSAP method and SAP method has the following steps: the conductor of the non-wiring part of the conductor layer stacked on the film is etched away to form a circuit. When the conductor of the non-wiring part cannot be removed and remains on the film, it becomes the cause of the circuit short circuit, so the conductor of the non-wiring part must be completely removed. Here, in the case of a film with a large surface roughness, the chemical copper plating layer (conductor layer) is incorporated into the depth of the concave part of the film surface, and the removal based on etching becomes difficult. When the etching is strengthened to completely remove the conductor of the non-wiring part incorporated into the depth of the film, there is a problem that the conductor of the wiring part will be etched until it is etched. In addition, when the difference in surface roughness between the length direction (MD) and the width direction (TD) is large, in order to completely remove the conductor, etching must be performed according to the large surface roughness. However, when etching is strengthened according to the large surface roughness, the conductor of the wiring part in the direction with a small surface roughness will be excessively etched, and the thickness of the wiring will become uneven in MD and TD. When a film having a large surface roughness or a large difference in surface roughness between MD and TD is used to manufacture a circuit substrate, there is a problem that the conductor of the wiring part is etched and a precise circuit cannot be formed. In contrast, the stretched liquid crystal polymer film of the present invention controls the surface roughness Ra measured by a laser microscope, so that during the manufacture of the circuit substrate, a conductor layer is formed on the surface of the stretched liquid crystal polymer film, and when the conductor is removed, the conductor is not likely to remain on the surface of the film. Therefore, the stretched liquid crystal polymer film of the present invention can be removed with a small amount of etching, and the conductor formed on the non-wiring part of the film can reduce the influence of etching on the wiring part, so that a circuit substrate with a precise circuit can be manufactured.
[0089] The circuit substrate of the present invention can be used for various transmission lines, such as coaxial lines, strip lines, microstrip lines, coplanar lines, parallel lines, etc., due to the property of low transmission loss when high-frequency signals flow through them. In addition, the circuit substrate of the present invention can be used for antennas and antenna devices in which antennas and transmission lines are integrated.
[0090] Antennas include waveguide slot antennas, horn antennas, lens antennas, printed antennas, triplate antennas, microstrip antennas, patch antennas, and other antennas utilizing millimeter waves and microwaves. When the circuit substrate of the present invention is used for an antenna, the circuit substrate is preferably a multilayer circuit substrate.
[0091] The circuit board of the present invention can be further used for sensors such as vehicle-mounted radars having semiconductor elements.
[0092] Example
[0093] Next, the present invention will be specifically described with reference to Examples, but the present invention is not limited to these.
[0094] <Film Formability>
[0095] The produced stretched liquid crystal polymer film was visually evaluated for uneven thickness, streaks, etc. The films obtained in Examples 10 to 14 were evaluated.
[0096] ◎: No uneven thickness or streaks, good.
[0097] ○: There is no uneven thickness, but light streaks are visible.
[0098] △: Uneven thickness and streaks are visible.
[0099] ×: Uneven thickness, large cracks.
[0100] <Melting Point of Film>
[0101] The endothermic peak temperature observed when the temperature of the prepared stretched liquid crystal polymer film was increased from 0° C. at 10° C. / min using a differential scanning calorimeter (manufactured by PerkinElmer Co., Ltd., model: DSC8500) was taken as the melting point.
[0102] <Surface roughness of thin films (laser type)>
[0103] The surface roughness Ra of the supported polymer film and the stretched liquid crystal polymer film was determined using a laser microscope (Keyence Corporation, model: VK-X3000) equipped with a white interferometer. The roughness curve was measured in a field of view of 1052×1404 μm under the conditions of a measurement reference length of 0.25 mm, an evaluation length of 1 mm, a cutoff value λc of 0.25 mm, and no cutoff value λs, and the arithmetic mean roughness was calculated to determine the surface roughness Ra. It should be noted that the surface roughness Ra was determined as follows: for the front and back sides of the film, it was determined in each longitudinal direction (MD) and width direction (TD) of the film.
[0104] <Surface roughness of thin films (contact type)>
[0105] A contact surface roughness measuring instrument (manufactured by TOSEI ENGINEERING CORP.), model: (SURFCOM1400D-3DF), with a stylus having a tip radius of 2 μm, was used to determine the surface roughness Ra of the stretched liquid crystal polymer film in accordance with JIS B0601:1994, with a measuring length of 4 mm and a cutoff λc of 0.8 mm. In the following, in order to distinguish it from the surface roughness Ra determined by the laser method, the surface roughness determined by the contact method is referred to as Ra'. The surface roughness Ra' is determined for the front and back sides of the film, respectively, along each longitudinal direction (MD) and width direction (TD) of the film. The films obtained in Examples 10 to 14, Comparative Example 4 and Reference Example 1 were evaluated.
[0106] <Degree of Planar Orientation of Film>
[0107] The stretched liquid crystal polymer film was subjected to extreme point measurement using a sample horizontal multifunctional X-ray diffractometer (Rigaku Corporation, model: Ultima IV) with the diffraction angle (2θ) fixed at 20°, X-ray target: Cu, voltage: 40 kV, current: 40 mA, α angle = 45°, β angle = 0 to 360° (the longitudinal direction of the film was 0°, and the step angle was 5°), to prepare an X-ray diffraction intensity curve. The integrated intensities of β = 45 to 135°, 135 to 225°, 225 to 315°, and 315 to 45° of the curve were obtained, and the integrated intensity in the longitudinal direction was the sum of the integrated intensities of β = 45 to 135° and β = 225° to 315°, and the integrated intensity in the width direction was the sum of the integrated intensities of β = 135 to 225° and β = 315 to 45°, and the plane orientation degree was obtained by the following formula (3). The thin films obtained in Examples 1 to 14, Comparative Example 4 and Reference Example 1 were evaluated.
[0108] Planar orientation degree = (integrated intensity in the length direction - integrated intensity in the width direction) / (integrated intensity in the length direction + integrated intensity in the width direction) (4)
[0109] <Comparison of tensile load of films>
[0110] The unstretched liquid crystal polymer film sample was cut into a sample with a width direction (TD) of 120 mm and a length direction (MD) of 25 mm. The sample was installed in a tensile testing machine (TENSILON A-500 manufactured by Orientec Co., Ltd.) with a chuck spacing of 20 mm and a stretching direction of TD. The tensile test was carried out at the specified stretching temperature and stretching speed in each embodiment and comparative example. From the results of the tensile test, an SS curve was obtained with the tensile stress under elongation of 0 mm to 60 mm (chuck spacing of 20 mm to 80 mm, 1 to 4 times) as the vertical axis and the elongation as the horizontal axis. The vertical axis of the SS curve of the unstretched liquid crystal polymer film was converted into a tensile load by multiplying the tensile stress of the unstretched liquid crystal polymer film by the cross-sectional area of the unstretched liquid crystal polymer film. For the supporting polymer film, a tensile test was also carried out in the same manner to obtain the SS curve and convert it into a tensile load. For each SS curve, the tensile load values of the unstretched liquid crystal polymer film and the supporting polymer film under the same elongation were compared in the range of elongation of 0 mm to 60 mm, and the evaluation was performed as follows. In Example 14 in which a laminated film was produced by coextrusion of a liquid crystal polymer and a support polymer, a tensile test was similarly performed using a support polymer layer peeled from the laminated film before stretching instead of the support polymer film to evaluate the tensile load.
[0111] 0: Over the entire range of elongation 0 mm to 60 mm, the tensile load of the supporting polymer film or supporting polymer layer is ≥ the tensile load of the unstretched liquid crystal polymer film
[0112] ×: In the range of elongation of 0 mm to 60 mm, the tensile load of the supporting polymer film or supporting polymer layer may be less than the tensile load of the unstretched liquid crystal polymer film.
[0113] <Linear Expansion Coefficient of Film>
[0114] The dimensional change was determined by placing a stretched liquid crystal polymer film (5 mm in width) on a thermomechanical analyzer (manufactured by Rigaku Corporation, model: TMA8310) (15 mm between chucks) and heating from 30°C to 150°C at 5°C / min while applying a load of 10 mN.
[0115] <Etching Removal Performance>
[0116] Assuming that a circuit substrate is manufactured according to the SAP method, the etching removal performance of the metal layer formed on the stretched liquid crystal polymer film is evaluated according to the following steps. First, for the stretched liquid crystal polymer films trial-produced in Examples 1 to 14 and Comparative Examples 3 and 4, a degreasing treatment, a Pd-based catalyst imparting treatment and an activation treatment are carried out by a known chemical plating method, and a metal layer with a thickness of 1 μm is formed on the surface of the activated film by chemical copper plating to obtain a laminate. Next, an etching bath containing 4.5 volume % of 35% hydrogen peroxide, 5 volume % of 98% sulfuric acid, and 30 g / L of copper sulfate / pentahydrate is prepared, and the laminate is immersed at 30°C to etch 1 μm. The etching removal performance is evaluated by confirming the presence or absence of copper residue on the surface of the stretched liquid crystal polymer film using an optical microscope (500 times). The results are shown in Table 3. It should be noted that in Table 3, any larger of the surface roughness Ra of MD and the surface roughness Ra of TD is recorded as the maximum value.
[0117] ◎: No copper residue on both surfaces.
[0118] ○: No copper residue was found on one surface, but copper residue was found on the other surface.
[0119] ×: Copper remains on both surfaces.
[0120] <Example 1>
[0121] A liquid crystal polymer (LAPEROS A950RX manufactured by Polyplastics Co., Ltd.) was supplied to a twin-screw extruder (screw diameter: 32 mm), extruded into a film from a T-die (lip length: 350 mm, lip gap: about 1 mm, die temperature: 300°C) at the front end of the extruder, and cooled to obtain an unstretched liquid crystal polymer film with a thickness of 75 μm.
[0122] Next, both sides of the unstretched liquid crystal polymer film and one side of the polyetheretherketone (PEEK) film (Victrex, APTIV Film 1000-025G, thickness 25 μm, surface roughness Ra = 0.14 μm (MD), 0.12 μm (TD)) as the supporting polymer film were subjected to direct atmospheric pressure plasma treatment in a gas atmosphere containing oxygen, with an electric power of 1.5 kW and a conveying speed of 1.0 m / min. Next, the plasma-treated surfaces were overlapped, and the PEEK film was thermally pressed onto both sides of the unstretched liquid crystal polymer film using a first roller heated to 305°C and a second roller heated to 120°C, under the conditions of a roller gap pressure of 0.2 MPa and a conveying speed of 0.5 m / min. The unstretched liquid crystal polymer film after thermal pressing was in close contact with the PEEK film.
[0123] From the laminated film thus prepared, a sample having a size of 150 mm in the width direction (TD) and 150 mm in the length direction (MD) was cut out. The sample was installed in a tensile testing machine (50 mm between chucks) in a manner that the stretching direction became TD, and after preheating at 100°C for 5 minutes in a constant temperature bath, it was stretched to 3 times (150 mm between chucks) at a stretching rate of 2500% / min. After that, the PEEK film was peeled off to obtain a stretched liquid crystal polymer film having a thickness of 25 μm, and the melting point, surface roughness Ra, plane orientation, and etching removal performance were evaluated. The results are shown in Result Tables 1 and 3.
[0124] For the above unstretched liquid crystal polymer film and PEEK film, as a tensile load comparison, after preheating at 100°C for 5 minutes (stretching temperature 100°C), they were stretched at a stretching speed of 2500% / min, and the SS curve was measured. The tensile load of the unstretched liquid crystal polymer film was compared with the tensile load of the PEEK film by the above method. The results are as follows: Figure 3 As shown, the tensile load of the PEEK film is higher than that of the liquid crystal polymer film. Figure 3 This is a graph comparing the tensile load of the unstretched liquid crystal polymer film in Example 1 and the tensile load of the PEEK film.
[0125] <Examples 2 to 6>
[0126] A stretched liquid crystal polymer film was obtained in the same manner as in Example 1 except that the supporting polymer film, stretching temperature, and stretching speed were changed as described in Table 1, and the stretched liquid crystal polymer film was evaluated in the same manner.
[0127] <Example 7>
[0128] A liquid crystal polymer stretched film was obtained in the same manner as in Example 1 except that a biaxially stretched PBT film (manufactured by KOHJIN Film & Chemicals Co., Ltd., BOBLET, thickness 25 μm) was used as the supporting polymer film and the temperature of the first roller during the thermal compression bonding was 200° C. and the evaluation was performed in the same manner. The results are shown in Tables 1 and 3.
[0129] <Example 8>
[0130] A biaxially stretched PET film with an easy-adhesive layer (Toyobo A4300, thickness 38 μm) was used instead of the PEEK film, and the surfaces of the unstretched liquid crystal polymer and the biaxially stretched PET film were not subjected to plasma treatment, and the first roller temperature was 200° C., and the stretched liquid crystal polymer film was obtained in the same manner as in Example 7, and the evaluation was performed in the same manner. The unstretched liquid crystal polymer film after the thermal compression was in close contact with the biaxially stretched PET film. The evaluation results of the stretched liquid crystal polymer film are shown in Result Tables 1 and 3.
[0131] <Example 9>
[0132] For one side of the unstretched liquid crystal polymer film and one side of the polyetheretherketone (PEEK) film (manufactured by Victrex, APTIV Film 1000-025G, thickness 50 μm, surface roughness Ra = 0.14 μm (MD), 0.12 μm (TD)) as a supporting polymer film, a direct atmospheric pressure plasma treatment was performed in a gas atmosphere containing oxygen with an electric power of 1.5 kW and a conveying speed of 1.0 m / min. Next, the plasma-treated surfaces were overlapped, and the PEEK film was hot-pressed onto one side (surface) of the unstretched liquid crystal polymer film using a first roller heated to 305°C and a second roller heated to 120°C under conditions of a roller gap pressure of 0.2 MPa and a conveying speed of 0.5 m / min to produce a two-layer laminated film of the unstretched liquid crystal polymer film and the supporting polymer film. In addition, a stretched liquid crystal polymer film was obtained in the same manner as in Example 3 and evaluated in the same manner. The results are shown in Result Tables 1 and 3.
[0133] <Example 10>
[0134] In the same manner as in Example 1, a laminated film was prepared in which PEEK films were thermally pressed onto both surfaces of an unstretched liquid crystal polymer film.
[0135] The laminated film thus prepared was stretched 3 times in the width direction (TD) at a conveying speed of 15 m / min (stretching speed 2500% / min, reaching stretching temperature 170°C) in a transverse stretching machine of a tenter frame type (furnace temperature 320°C), and the PEEK film was peeled off to obtain a stretched liquid crystal polymer film with a thickness of 25 μm. The stretching reaching temperature refers to the temperature of the laminated film at the end of stretching. The film forming properties, melting point, surface roughness Ra and Ra', plane orientation, and linear expansion coefficient of the film were evaluated. Furthermore, after the film was heat treated at 250°C for 24 hours, the linear expansion coefficient was evaluated. Furthermore, for the unstretched liquid crystal polymer film and the PEEK film used in this embodiment, the tensile load at the reaching stretching temperature and the stretching speed in this embodiment was measured and evaluated. The results are shown in Result Tables 1 and 3.
[0136] <Examples 11-12>
[0137] A stretched liquid crystal polymer film was obtained in the same manner as in Example 10 except that the conveying speed was changed to 5 m / min (stretching speed 833% / min, reaching a stretching temperature of 240°C) and 1 m / min (stretching speed 167% / min, reaching a stretching temperature of 290°C). The film forming properties, melting point, surface roughness Ra and Ra', plane orientation, linear expansion coefficient, tensile load, and etching removal performance of the film were evaluated. The results are shown in Tables 1 and 3.
[0138] <Example 13>
[0139] A stretched liquid crystal polymer film having a thickness of 25 μm was obtained in the same manner as in Example 11 except that a polyetheretherketone (PEEK) film having a surface roughness Ra of 0.96 μm (MD) and 1.04 μm (TD) (manufactured by Shin-Etsu Polymer Co., Ltd., with a thickness of 25 μm) was used. The film forming properties, melting point, surface roughness Ra and Ra', plane orientation, linear expansion coefficient, tensile load, and etching removal performance of the film were evaluated. The results are shown in Result Tables 1 and 3.
[0140] <Example 14>
[0141] A liquid crystal polymer (LAPEROS A950RX manufactured by Polyplastics Co., Ltd.) was supplied to a twin-screw extruder (screw diameter 32 mm) and melt-kneaded at 300° C. In addition, a polyetheretherketone (PEEK) polymer (VESTAKEEP 3300G manufactured by Diacel Evonik) as a supporting polymer was supplied to a single-screw extruder (screw diameter 40 mm) and melt-kneaded at 380° C. These molten polymers were supplied to a multi-manifold T-die, and the layers formed by the supporting polymer were overlapped on both sides of the layer formed by the liquid crystal polymer, extruded, and cooled, thereby producing a laminated film having a liquid crystal polymer layer of 75 μm, supporting polymer layers on both sides of 25 μm, and a total of 125 μm.
[0142] The laminated film thus prepared was stretched 3 times in the width direction (TD) in a transverse stretching machine (furnace temperature 320°C) at a conveying speed of 5m / min (stretching speed 833% / min, reaching a stretching temperature of 240°C), and the PEEK film was peeled off to obtain a stretched liquid crystal polymer film with a thickness of 25μm. The film forming properties, surface roughness Ra and Ra', plane orientation, linear expansion coefficient, tensile load, and etching removal performance of the film were evaluated. The results are shown in Result Tables 1 and 3.
[0143] [Table 1]
[0144]
[0145] <Comparative Example 1>
[0146] An unstretched liquid crystal polymer film was obtained in the same manner as in Example 1. A sample having a size of 150 mm in the width direction (TD) and 150 mm in the length direction (MD) was cut out from the film. The sample was mounted in a tensile testing machine (50 mm between chucks) in such a way that the stretching direction became TD, and after preheating at 150°C for 5 minutes in a thermostatic bath, it was stretched to 3 times at a stretching speed of 2500% / min, but the liquid crystal polymer film broke, and the surface roughness Ra and plane orientation of the film could not be evaluated. The results are shown in Table 2.
[0147] <Comparative Example 2>
[0148] In the same manner as in Example 1, an unstretched liquid crystal polymer film was obtained.
[0149] A porous polytetrafluoroethylene (PTFE) film with a thickness of 100 μm and a specific gravity of 1.9 is laminated on both sides of the unstretched liquid crystal polymer film. The porous PTFE film is hot-pressed on both sides of the unstretched liquid crystal polymer film using a first roller heated to 305°C and a second roller heated to 120°C, with a roller gap pressure of 0.2 MPa and a conveying speed of 0.5 m / min. A sample with a size of 150 mm in the width direction (TD) and 150 mm in the length direction (MD) is cut out from the laminated film made in this way. The sample is installed in a tensile testing machine (50 mm between chucks) in a way that the stretching direction becomes TD. After preheating at 150°C for 5 minutes in a thermostatic bath, it is stretched to 3 times at a stretching speed of 2500% / min. As a result, the porous PTFE film layer of the laminated film can be stretched, but the liquid crystal polymer film layer is broken, and the surface roughness and plane orientation of the film cannot be evaluated. The results are shown in Table 2.
[0150] For the above unstretched liquid crystal polymer film and porous PTFE film, as a tensile load comparison, after preheating at 150°C for 5 minutes, they were stretched at a stretching rate of 2500% / min, and the SS curve was measured. Next, the tensile load of the unstretched liquid crystal polymer film was compared with the tensile load of the porous PTFE film by the above method. The results are as follows: Figure 4 As shown in FIG. 1 , the tensile load of the porous PTFE film is lower than that of the liquid crystal polymer film. Figure 4 This is a graph comparing the tensile load of the unstretched liquid crystal polymer film and the tensile load of the porous PTFE film in Comparative Example 2.
[0151] <Comparative Example 3>
[0152] As shown in Table 2, the stretching temperature and stretching speed were changed. In addition, in the same manner as in Comparative Example 2, a film having a porous polytetrafluoroethylene (PTFE) film laminated on both sides of the unstretched liquid crystal polymer film was stretched. A stretched liquid crystal polymer film was obtained without breaking the liquid crystal polymer film layer, but the thickness of the film was uneven and the surface roughness Ra was higher than 0.5 μm. The evaluation results of the melting point, surface roughness Ra and Ra', and tensile load are shown in Table 2. In addition, the evaluation results of the etching removal performance are shown in Table 3.
[0153] <Comparative Example 4>
[0154] A stretched liquid crystal polymer film having a thickness of 25 μm was obtained in the same manner as in Example 11 except that a polyetheretherketone (PEEK) film having a surface roughness Ra exceeding 1.5 μm (manufactured by Shin-Etsu Polymer Co., Ltd., with a thickness of 25 μm) was used. The surface roughness Ra of the film was higher than 0.5 μm. The evaluation results of the melting point, surface roughness Ra and Ra', plane orientation, linear expansion coefficient, and tensile load are shown in Table 2. In addition, the evaluation results of the etching removal performance are shown in Table 3.
[0155] <Reference Example 1>
[0156] The melting point, surface roughness and plane orientation of the unstretched liquid crystal polymer film with a thickness of 75 μm prepared in Example 1 were measured. In addition, the film was heat treated at 250° C. for 24 hours, and the linear expansion coefficient was evaluated. The results are shown in Table 2. In addition, the evaluation results of the etching removal performance are shown in Table 3.
[0157] [Table 2]
[0158]
[0159] [Table 3]
[0160] Table 3
[0161]
[0162] As shown in Table 1, the stretched liquid crystal polymer films of Examples 1 to 13 obtained by laminating a film formed of a supporting polymer film having a surface roughness Ra of 1.5 μm or less to a film formed of a liquid crystal polymer and forming a laminated film, stretching the formed laminated film, and peeling off the supporting polymer film, and the stretched liquid crystal polymer film of Example 14 obtained by overlapping and extruding a liquid crystal polymer and a supporting polymer from a T-die to form a laminated film, stretching the formed laminated film, and peeling off the supporting polymer layer, all have a surface roughness Ra of 0.5 μm or less, which is good smoothness. In addition, the larger value of the surface roughness Ra (MD) in the longitudinal direction and the surface roughness Ra (TD) in the width direction of the stretched liquid crystal polymer films of Examples 1 to 14 is less than 0.7 μm, and the difference between the surface roughness Ra (MD) and the surface roughness Ra (TD) is less than 0.15 μm, and has good smoothness. In addition, as shown in Table 3, in Examples 1 to 14, there is no copper residue on at least one surface of the stretched liquid crystal polymer film after etching the laminate, and the etching removal performance is excellent.
[0163] In detail, if the examples 1 to 4 in which the stretching speed is 2500% / min and the stretching temperature is changed from 100°C to 250°C are compared, the surface roughness Ra of the stretched liquid crystal film obtained at the stretching temperature of 100°C is as small as 0.11 to 0.15 μm, but the plane orientation degree is as high as 0.25. The higher the stretching temperature, the larger the surface roughness Ra, while on the other hand, the plane orientation degree becomes smaller. At the stretching temperature of 250°C, the surface roughness Ra becomes 0.21 to 0.3 μm, and the plane orientation degree becomes 0.1. In addition, in the example 5 in which the stretching temperature is 150°C and the stretching speed is as low as 50% / min, the surface roughness Ra does not change significantly compared with the example 2 in which the stretching temperature is 150°C and the stretching speed is 2500% / min, but the plane orientation degree becomes smaller. In the example 6 in which the stretching temperature is further increased to the melting point of the liquid crystal polymer to 280°C, the surface roughness Ra becomes as high as 0.26 to 0.32 μm, but the plane orientation degree is reduced to 0.01. The lower the stretching temperature, the harder the film, the more stable the shape of the film after stretching, and the smaller the surface roughness Ra. However, the molecular motion decreases, so it is believed that the molecular orientation (MD) before stretching is less likely to change and the plane orientation degree increases.
[0164] In addition, when a polymer other than PEEK is used as a supporting polymer (Examples 7 and 8), a stretched liquid crystal film can also be obtained. By using a supporting polymer film further provided with an easy-adhesion layer, a stretched liquid crystal film can also be obtained without surface treatment such as plasma treatment. (Example 8) Furthermore, when the supporting polymer film is only one-sided (Example 9), a stretched laminated film is obtained in which the surface roughness Ra of the surface without supporting polymer stacking is large, but the surface roughness Ra of the surface stacked with supporting polymer is less than 0.5 μm.
[0165] In the case of stretching using a transverse stretching machine in a tentering method (Examples 10 to 12), the lower the stretching temperature and the higher the stretching speed, the smaller the surface roughness Ra and the higher the plane orientation. In addition, the lower the stretching temperature and the higher the stretching speed, the better the film-forming properties of the film. The surface roughness Ra' of these films measured by a contact surface roughness meter is in the range of 0.09 to 0.15 μm, and no correlation with the stretching temperature and stretching speed that is visible in the surface roughness Ra measured by a laser microscope is observed. It is considered difficult to measure accurate surface roughness using a contact surface roughness meter.
[0166] A stretched polymer film (Example 14) was also obtained using a co-extruded film of a liquid crystal polymer and a supporting polymer (PEEK), and the surface roughness Ra was basically the same as that of a laminated film of a stretched liquid crystal polymer film and a supporting polymer film stretched under the same conditions (Example 13).
[0167] On the other hand, as shown in Comparative Example 1 in Table 2, when a film composed only of an unstretched liquid crystal polymer was stretched, the film broke, and the surface roughness and the degree of plane orientation could not be evaluated.
[0168] As shown in Comparative Example 2, when the total tensile load of the supporting film was lower than the tensile load of the unstretched liquid crystal polymer film, the liquid crystal polymer film was broken during stretching.
[0169] As shown in Comparative Example 3, the surface roughness Ra' of the stretched liquid crystal polymer film obtained by stretching a laminated film bonded with a porous PTFE film above the melting point of the liquid crystal polymer measured by a contact surface roughness meter becomes less than 0.5 μm, but the surface roughness Ra measured by a laser microscope becomes more than 0.5 μm. In addition, as shown in Comparative Example 4, when a polyetheretherketone (PEEK) film is used as a supporting polymer film, a laminated film bonded with a polyetheretherketone film having a surface roughness Ra exceeding 1.5 μm is stretched, and as a result, the surface roughness Ra measured by a laser microscope also becomes more than 0.5 μm.
[0170] In addition, as shown in Table 3, in Comparative Examples 3 and 4 where the surface roughness Ra exceeds 0.5 μm and the larger of the surface roughness Ra (MD) in the length direction and the surface roughness Ra (TD) in the width direction is greater than 0.7 μm, copper remains on both sides of the stretched liquid crystal polymer film after the laminate is etched, resulting in poor etching removal performance.
[0171] As shown in Reference Example 1, the surface roughness Ra of the unstretched liquid crystal polymer film is less than 0.5 μm, but the plane orientation degree is as large as 0.71, the expansion coefficient in the linear length direction (MD) becomes -21.7 ppm, and the expansion coefficient in the width direction (TD) becomes 80.3 ppm, and the anisotropy of the linear expansion coefficient becomes larger.
Claims
1. A stretched liquid crystal polymer film, which is a stretched liquid crystal polymer film formed of a liquid crystal polymer, wherein the surface roughness Ra of at least one surface of the stretched liquid crystal polymer film measured by a laser microscope is 0.5 μm or less.
2. A stretched liquid crystal polymer film, which is a stretched liquid crystal polymer film formed of a liquid crystal polymer, wherein: For at least one side, the larger of the surface roughness Ra(MD) in the length direction and the surface roughness Ra(TD) in the width direction of the film measured by a laser microscope is less than 0.7 μm, and the absolute value of the difference between the Ra(MD) and the Ra(TD) is less than 0.15 μm.
3. The stretched liquid crystal polymer film according to claim 1 or 2, wherein: In the extreme point measurement based on X-ray diffraction, when the film is rotated in the in-plane direction, i.e., the β direction, while being tilted at 45° (α=45° in the Schulz method) and the diffraction intensity of the 110 plane is measured, the longitudinal direction of the film is set to β=0°, and the integrated intensities of β=45 to 135°, 135° to 225°, 225 to 315°, and 315 to 45° are obtained, and the sum of the integrated intensity of β=45 to 135° and the integrated intensity of β=225° to 315° is set as the integrated intensity in the longitudinal direction, and the sum of the integrated intensity of β=135 to 225° and the integrated intensity of β=315 to 45° is set as the integrated intensity in the width direction, the plane orientation degree represented by the following formula (1) is not less than -0.5 and not more than 0.5, Planar orientation degree=(integrated intensity in the longitudinal direction−integrated intensity in the width direction) / (integrated intensity in the longitudinal direction+integrated intensity in the width direction) (1).
4. A method for producing a stretched liquid crystal polymer film, comprising the following steps: In a first step, a support film formed of a support polymer and having a surface roughness Ra of 1.5 μm or less measured by a laser microscope is bonded to at least one side of an unstretched liquid crystal polymer film formed of a liquid crystal polymer to obtain a laminated film; A second step of stretching the laminated film at least in the width direction; and In the third step, the stretched support film is peeled off.
5. A method for producing a stretched liquid crystal polymer film, comprising the following steps: In a first step, a molten liquid crystal polymer and a supporting polymer are extruded into a film using an extruder in such a manner that a layer formed by the supporting polymer is laminated on at least one side of a layer formed by the liquid crystal polymer, thereby obtaining a laminated film; A second step of stretching the laminated film at least in the width direction; and In the third step, the stretched layer composed of the supporting polymer is peeled off.
6. The method for producing a stretched liquid crystal polymer film according to claim 4, wherein: The first step includes the step of subjecting a surface of the unstretched liquid crystal polymer film and a surface of the support film to be bonded to each other before bonding the support film to the unstretched liquid crystal polymer film.
7. The method for producing a stretched liquid crystal polymer film according to claim 6, wherein: The surface treatment is one selected from the group consisting of plasma treatment, corona treatment and chemical treatment.
8. The method for producing a stretched liquid crystal polymer film according to any one of claims 4 to 7, wherein: The second step includes the step of stretching at a temperature lower than the melting point of the liquid crystal polymer.
9. The method for producing a stretched liquid crystal polymer film according to any one of claims 4 or 6 to 8, wherein: In the second step, a tensile load calculated by multiplying the tensile stress of the support film at the temperature during stretching by the cross-sectional area of the support film is greater than or equal to a tensile load calculated by multiplying the tensile stress of the unstretched liquid crystal polymer film at the temperature during stretching by the cross-sectional area of the unstretched liquid crystal polymer film.
10. The method for producing a stretched liquid crystal polymer film according to claim 5, wherein: In the second step, a tensile load calculated by multiplying the tensile stress of the layer formed by the supporting polymer at the temperature during stretching by the cross-sectional area of the layer formed by the supporting polymer is greater than or equal to a tensile load calculated by multiplying the tensile stress of the layer formed by the liquid crystal polymer at the temperature during stretching by the cross-sectional area of the layer formed by the liquid crystal polymer.
11. The method for producing a stretched liquid crystal polymer film according to any one of claims 4 to 10, wherein: The supporting polymer is an aromatic polyetherketone or a polyester.
12. The method for producing a stretched liquid crystal polymer film according to claim 11, wherein: The polyester is at least one polymer selected from the group consisting of polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate.
13. A laminate comprising: A film layer comprising the stretched liquid crystal polymer film according to any one of claims 1 to 3, and a metal layer. 14 . A circuit board comprising the laminate according to claim 13 .
Citation Information
Patent Citations
Liquid crystal polymer film and production thereof
JP1995323506A
Liquid crystal polymer film and its laminate
JP1998034742A
Wiring board and manufacturing method thereof
JP2006179609A
Manufacturing method of thermoplastic resin film, and the thermoplastic resin film
JP2007090540A
Single-sided metal-clad laminated sheet and method for producing the same
JP2016107505A